2017
DOI: 10.4088/jcp.16r11332
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Antidepressant Effects of Acute Sleep Deprivation

Abstract: These findings support a significant effect of sleep deprivation and suggest the need for future studies on the phenotypic nature of the antidepressant response to sleep deprivation, on the neurobiological mechanisms of action, and on moderators of the sleep deprivation treatment response in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 0 publications
4
78
1
1
Order By: Relevance
“…In the present cohort the proportion of response to SD was on the higher end of the range reported in a recent meta-analysis, in which response rates ranged from 7-78% (Boland et al, 2017). The authors hypothesized that the small individual sample sizes were likely to contribute to this wide range of response rates.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In the present cohort the proportion of response to SD was on the higher end of the range reported in a recent meta-analysis, in which response rates ranged from 7-78% (Boland et al, 2017). The authors hypothesized that the small individual sample sizes were likely to contribute to this wide range of response rates.…”
Section: Discussionmentioning
confidence: 44%
“…Therapeutic sleep deprivation (SD) reliably induces rapid and substantial antidepressant effects in the majority of patients with a major depressive episode (Benedetti et al, 2007;Benedetti and Colombo, 2011;Gillin, 1983;Wu and Bunney, 1990). A recent meta-analysis of SD studies showed an average response rate of approximately 50% with significant variability, with up to 78% of patients responding to SD treatment (Boland et al, 2017). Although its therapeutic value is limited due to relapse after recovery sleep (Giedke and Schwärzler, 2002;Wu et al, 1990), SD is particularly unique in its defined immediate positive effect on depressive mood and may therefore offer unique insights about the biological factors underlying depression.…”
Section: Introductionmentioning
confidence: 99%
“…19 Its effectiveness has also been demonstrated by a meta-analysis. 44 Furthermore, BLT may be performed in combination with SD to enhance and maintain the effect of SD. 35,45 Thus, the combination of different chronotherapies is a viable treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the same year that the two-process model was published, Borbely and Wirz-Justice [14] also proposed the S-deficiency hypothesis of depression, which posits that individuals with depression do not build an adequate sleep drive during the course of a normal day of waking. This hypothesis is said to account for several key findings in depression, including sleep disturbances like delayed sleep onset and increased sleep fragmentation, as well as the finding that total sleep deprivation paradoxically alleviates depressive symptoms in 50% of individuals [1517]. In order to test this hypothesis, several groups have attempted to use more objective measures to examine sleep homeostasis in depression.…”
Section: Models Of Sleep and Swamentioning
confidence: 99%